A rapid, straightforward, and print house compatible mass fabrication method for integrating 3D paper‐based microfluidics. Issue 20 (7th October 2013) - Xiao, Liangpin; Liu, Xianming; Zhong, Runtao; Zhang, Kaiqing; Zhang, Xiaodi; Zhou, Xiaomian; Lin, Bingcheng; Du, Yuguang
<x xml:space="preserve">Abstract</x> Three‐dimensional (3D) paper‐based microfluidics, which is featured with high performance and speedy determination, promise to carry out multistep sample pretreatment and orderly chemical reaction, which have been used for medical diagnosis, cell culture, environment determination, and so on with broad market prospect. However, there are some drawbacks in the existing fabrication methods for 3D paper‐based microfluidics, such as, cumbersome and time‐consuming device assembly; expensive and difficult process for manufacture; contamination caused by organic reagents from their fabrication process. Here, we present a simple printing–bookbinding method for mass fabricating 3D paper‐based microfluidics. This approach involves two main steps: (i) wax‐printing, (ii) bookbinding. We tested the delivery capability, diffusion rate, homogeneity and demonstrated the applicability of the device to chemical analysis by nitrite colorimetric assays. The described method is rapid (<30 s), cheap, easy to manipulate, and compatible with the flat stitching method that is common in a print house, making itself an ideal scheme for large‐scale production of 3D paper‐based microfluidics.